A comparative study on placebo and trenaxamic acid for the prophylaxis is of post-partum hemorrhage: a randomised double-blind control study - Parveen, S.; Chandra, G. Kesava; Reddy, K. Ravindra; Kavya Sree, A. V.; Varalakshmi, M.; Gayathri, R.; Chandra, V. Bhuvana; Ramana, P. Venkata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Obstetric haemorrhage accounts for 20-25% of maternal mortality and morbidity. Anti-fibrinolytics are being widely used in field of surgery. It is also used to reduce heavy menstrual blood loss. The aim of this study was to analyse the effectiveness of TXA in reducing blood loss during normal vaginal delivery. Methods: The randomized double-blind control study was done in the Labour ward. It was conducted on 100 women undergoing Normal vaginal delivery. They were allocated to either Study or Control group by randomization. TXA was given during the Third stage of delivery in study group in addition to the routine care whereas the control group had routine care alone. Blood loss was measured in both groups by bag method. Results: The significant of reduction in blood loss calculated from placental delivery to 2hrs. 141.9 ml in study group versus 270.4 ml in control group. Among primi patients, the control group average blood loss was 325ml, the study group avg blood loss was 169ml. Among G2 patients, the control group average blood loss was 248.5ml. The study group average blood loss was 128.25ml. Among G3 patients, the control group average blood loss was 203ml, the study group average blood loss was 115ml. Conclusions: TXA significantly reduced the amount of blood loss during normal vaginal delivery. Thus, TXA can be used safely and effectively in subjects undergoing normal vaginal delivery.